Macroautophagy is involved in residual bodies formation during spermatogenesis in sea urchins, Strongylocentrotus intermedius. (February 2019) - Kalachev, Alexander V.; Yurchenko, Olga V.; Kiselev, Konstantin V.
Highlights: Excessive cytoplasm in spermatids is sequestered in vesicles, surrounded by a double membrane. Morphology of the vesicles is similar to autophagosomes. In Strongylocentrotus intermedius, the residual bodies discarded from spermatids are LC3-positive. Abstract: An ultrastructural study of developing spermatids in sea urchins, Strongylocentrotus intermedius, showed that macroautophagy is involved in formation of residual bodies and removal of excessive cytoplasm by spermatids during spermatogenesis in this species. During late stages of spermatogenesis spermatids sequester excessive cytoplasm into vesicles, surrounded by a double membrane. Subsequently, these vesicles fused to one another into larger vacuoles, up to 1.5 μm in diameter. Finally, the vacuoles transformed into residual bodies by condensing their content into finely granular material of varying electron density, separated from cytoplasm by a single membrane. An immunoelectron microscopic study of late spermatids with the antibodies, raised against microtubule-associated protein 1 A/1B-light chain 3 (LC3), which is a marker of autophagosomes, showed that residual bodies in late spermatids of S . intermedius were LC3-positive.